Study of microwave absorption properties of strontium hexaferrite (SrFe12O19) and impure activated carbon composite in X-band range (8.2 – 12.4 GHz) - Jacob Rosarian Joy S; D. Rajan Babu (Results in Physics)
A novel composite material composed of Impure Activated carbon and strontium hexaferrite (SrFe12O19) was synthesized and characterized for enhanced microwave absorption in the (8.2–12.4 GHz) X-band frequency region. A simple synthesis procedure was employed to ensure that both components are evenly distributed throughout the composite. The complex permittivity and permeability values were obtained and studied. Reflection loss (RL) was used as the main performance parameter for analysing the microwave absorption properties using a vector network analyzer. The significant reflection loss of −73.29 dB at a thickness of 4 mm demonstrated the composite material’s exceptional microwave absorption property. The findings indicate that the synergistic interaction between strontium hexaferrite and Impure activated carbon was the primary factor contributing to the enhanced performance.